Precious resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Following in the footsteps of Cameroon (see Spore 86), now Guyana plans to forbid the export of logs of two precious timbers: courbaril wood (Hymenaea courbaril) and Guyana crab wood (Carapa guianensis). Henceforth they are to be processed...